Can impoverished family nurture rich sons any more? The effect of household income on intergenerational transmission of education: Evidence from China - Li, Xiaofan; Xie, Weiwei; Wang, Lu; Zou, Tingting (Frontiers in Psychology, 2023)
Family investment in education is an important variable influencing the educational attainment of children. Family investment in education is influenced by family income, and the increase in family income gap will aggravate the inequity of education and enhance the degree of intergenerational transmission of education. But the above theories need to be further tested in reality. This paper uses the 2018 China Family Panel Studies (CFPS) to verify the role of Chinese family income on intergenerational transmission of education through the education transition matrix and the mediating effect model, and examines the effect of college expansion policy on the mediating effect of family income on intergenerational transmission of education. The results show that: (1) The education level of parents has obvious transmissibility to the education level of children. The solidification rate of intergenerational transmission of education between parents and children is 25.72%, the upward mobility rate is 60.58% and the downward mobility rate is 13.70%. (2) The mediating effect model shows that the total effect of the father's education level on children's education level is 0.279 and the direct effect is 0.272, and the family income plays a mediating effect in the intergenerational transmission of education, and the mediating degree reaches about 2.6%. (3) The expansion of higher education provides more opportunities for children of society, especially lower-middle-income families, to receive higher education, which weakens the mediating effect of family income in the intergenerational transmission of education. The findings of this paper provide support for policymakers to increase public investment in education.